“Pretty and productive!” an exploratory study on the viewing engagement of aesthetic study YouTube vlogs’ amongst Filipino college viewers and their study and purchasing habits - Alvarez, Antonette Macey
This dissertation examines the manner of consumption that Filipino College Viewers participate in when watching Aesthetic Study Youtube Vlogs in relation to their academic experiences and purchasing habits. Aesthetic Study Youtube Vlogs have risen in popularity as accompaniment learning media, characterized by kempt, desaturated, and symmetrical work spaces and extensive continuous studying hours. Furthermore, they promoted the use of digital products, cafe and caffeine products, and other visually pleasing items to incentivize a productive lifestyle from students. Based on the Consumer Culture Theory, these videos were avenues for overly-romanticizing the academic environment at the cost of audience comfort, accessibility, and confidence. To explore how audiences use these videos to pattern their understanding of student identity both in their routine and purchases, the dissertation analyzed eighteen Aesthetic Study Youtube Vlogs for their structure, messaging, and endorsements. Additionally, the dissertation also interviewed fourteen Filipino College Students who have watched these videos to analyze their experiences with the content. Audiences found Aesthetic Study Youtube Vlogs to be conducive to forming their student identity based on the creator’s standards, but showed hesitance in making purchases paralleled to the content. The study then proposes a framework dissecting audience reception and interpretation of habits based on media consumption.